2018
DOI: 10.1371/journal.pone.0193704
|View full text |Cite
|
Sign up to set email alerts
|

Citrus aurantium L. dry extracts promote C/ebpβ expression and improve adipocyte differentiation in 3T3-L1 cells

Abstract: Metabolic and/or endocrine dysfunction of the white adipose tissue (WAT) contribute to the development of metabolic disorders, such as Type 2 Diabetes (T2D). Therefore, the identification of products able to improve adipose tissue function represents a valuable strategy for the prevention and/or treatment of T2D. In the current study, we investigated the potential effects of dry extracts obtained from Citrus aurantium L. fruit juice (CAde) on the regulation of 3T3-L1 cells adipocyte differentiation and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Indeed, an increasing number of studies have reported that several natural food-derived compounds modulate miRNA expression in different animal cells and tissues [24][25][26]. Extracts from Citrus aurantium L. have been recently used for investigating adipocyte differentiation [28,42,43]. However, quite different results have been obtained, and whether or not extracts from Citrus aurantium L. have pro-or anti-adipogenic properties is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, an increasing number of studies have reported that several natural food-derived compounds modulate miRNA expression in different animal cells and tissues [24][25][26]. Extracts from Citrus aurantium L. have been recently used for investigating adipocyte differentiation [28,42,43]. However, quite different results have been obtained, and whether or not extracts from Citrus aurantium L. have pro-or anti-adipogenic properties is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As well as this, nutraceuticals are known to regulate adipocyte cell line activity [ 27 ]. In line with this, we have recently demonstrated the nutraceutical properties of CA de, a dry extract preparation obtained from Citrus aurantium L. ( CA de) fruit juice, on the regulation of 3T3-L1 cell adipocyte differentiation and function [ 28 ]. CA de enhances in vitro terminal adipocyte differentiation of 3T3-L1 pre-adipocytes in terms of increased gene expression of Pparγ , glucose transporter type 4 ( Glut4 ), and fatty acid-binding protein 4 ( Fabp4 ), as well as the functional capacity of 3T3-L1 mature adipocytes in terms of improved insulin-induced glucose uptake [ 28 ].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations